Epidemiological features of human brucellosis in Tongliao City, Inner Mongolia province, China: a cross-sectional study over an 11-year period (2007–2017) - Jingbo Zhai; Bin Zhang; Di Li; Lifei Li; Lingzhan Wang (BMJ Open)
Objectives To describe the epidemiology of human brucellosis in the past decade and provide evidence of disease control in Tongliao city, which is one of the highest-risk areas of human brucellosis in Inner Mongolia province, China.Design Cross-sectional study.Participants Clinically and bacteriologically confirmed human brucellosis cases.Primary and secondary outcome measures An analysis of the reported cases of human brucellosis during 2007–2017 was carried out to describe the age, sex and occupational distributions of the cases. The time series analysis model and the geographical information system were explored to describe the seasonality and spatiotemporal distribution, respectively, at the county level.Results A total of 13 938 cases of human brucellosis was collected in Tongliao from 2007 to 2017; the majority was aged 25 years to 59 years (85.4%) and the male-to-female ratio was 2.64:1; most of them were agriculturalists (81.9%) and pastoralists (12.4%). The incidence rates increased dramatically from 9.22/100 000 in 2007 to 69.16/100 000 in 2011 with an annual increase of 14.99%. They decreased during 2012–2016 (annual decrease of 8.37%) and rose again in 2017 (44.32/100 000). The disease peaked during March–July, with a clear periodicity and trend of monthly anterior displacement since 2012. Jarud Banner, the region located in the north-west of Tongliao, had the highest accumulated incidence rate (130.1/100 000) compared with other counties. The high-risk regions were spread from the north-west to the south and east of Tongliao during the past decade.Conclusions The prevalence of human brucellosis in Tongliao was aggravated during the past decade and peaked during March–July. High-risk areas were mainly concentrated in the counties with extensive prairies and livestock.